The influence of time and visualization on neurofeedback-guided parietal alpha downregulation and sense of presence in virtual reality - Botrel, Loic; Kreilinger, Alex; Müller, Mathias; Pfeiffer, Maria; Scheu, Vincent; Vowinkel, Nico; Zechner, Roland; Käthner, Ivo; Kübler, Andrea (Frontiers in Neuroscience, 2025)
In an EEG-based near real-time neurofeedback (NF) study in two parts using high immersive virtual reality (VR) we successfully trained healthy participants to downregulate their parietal alpha power, a neurophysiological correlate previously associated with enhanced sense of presence. The first part included n = 10 participants equipped with 128 and 64 channels gel-based active EEG electrodes in 10 sessions using standard bar feedback presented on a computer monitor. Nine participants were better than random at the 10th session and four improved over time. For the second part we reduced the electrode subset to 9 sponge-based active channels (2 frontal, 7 parietal around Pz) and a portable amplifier. Participants (n = 10) were trained each session within VR using bar feedback projected on a wall in the first 5 sessions and then controlling the flow of a water fountain. Participants were able to significantly downregulate their parietal alpha power after 5 sessions and learning occurred at the group level, with 7 participants showing both improvement over time and ability to modulate. However, these results were only shown during the fountain feedback and both ability and learning were non-significant in the VR projector condition. Based on self-reports, after excluding participants performing movements and closing their eyes, no particular mental strategy, such as relaxation, breathing or mental calculus was identified to help with alpha modulation. The hypothesized behavioral effect on sense of presence was not found nor any neurophysiological changes in fronto-parietal connectivity. While NF did not improve the sense of presence, we succeeded in adapting real-time NF training for high immersive VR technology via seamlessly embedded feedback in the form of a water fountain. The study showcases that NF is possible with sponge electrodes and portable EEG that would prove convenient in end-user (at home) or clinical setup. The dataset is publicly available on Openneuro.org.